Analisis Motivasi Belajar Biologi Siswa Ditinjau dari Model ARCS di Kelas XI SMAN 1 Tinambung - Sufyan Hakim; Muh. Rizal Kurniawan Yunus (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Learning motivation is a key factor in the success of Biology learning; however, it remains suboptimal among students in Indonesia, particularly in West Sulawesi. This study aims to analyze the Biology learning motivation of eleventh-grade students at SMAN 1 Tinambung based on the ARCS model (Attention, Relevance, Confidence, and Satisfaction). The study employed a quantitative descriptive approach. The sample consisted of 154 students selected using a total sampling technique. The instrument was an ARCS-based learning motivation questionnaire comprising 40 Likert-scale items that had been proven reliable. The results showed that students’ learning motivation was in the moderate category (mean = 3.10). The Relevance aspect obtained the highest score (3.35), while Confidence was the lowest (2.92). These findings indicate that students are able to understand the relevance of Biology to their daily lives; however, they still exhibit weaknesses in self-confidence and attention. Therefore, instructional strategies such as scaffolding, positive feedback, and varied teaching methods are needed to improve students’ learning motivation.